Electrical properties of silver Schottky contacts to ZnO thin films - 李新坤 李清山 梁德春 徐言东 (Optoelectronics letters, 2009)
ZnO thin films are deposited on Al/Si substrates by the pulsed laser deposition （PLD） method. The XRD and SEM images of films are examined. Highly c-axis oriented ZnO thin films which have uniform compact surface morphology are fabricated. The size of surface grains is about 30 nm. The Schottky barrier ultraviolet detectors with silver Schottky contacts are made on ZnO thin films. The current-voltage characteristics are measured. The ideality contact factor between Ag and ZnO film is 1.22, while the barrier height is 0.908 e V. After annealing at 600 ℃ for 2h, the ideality factor is 1.18 and the barrier height is 0.988 eV. With the illumination of 325 nm wavelength UV-light, the photocurrent-to-dark current ratios before and after annealing are 140.4 and 138.4 biased at 5 V, respectively. The photocurrents increase more than two orders of magnitude over the dark currents.